Rats and the city : Implications of urbanization on zoonotic disease risk in Southeast Asia - Kim R., Blasdell; Serge, Morand; Susan G. W., Laurance; Stephen L, Doggett; Amy, Hahs; Kelly, Trinh; David, Perera; Cadhla, Firth (PNAS, 2022)
Urbanization is rapidly transforming much of Southeast Asia, altering the structure and function of the landscape, as well as the frequency and intensity of the interactions between people, animals, and the environment. In this study, we explored the impact of urbanization on zoonotic disease risk by simultaneously characterizing changes in the ecology of animal reservoirs (rodents), ectoparasite vectors (ticks), and pathogens across a gradient of urbanization in Kuching, a city in Malaysian Borneo. We sampled 863 rodents across rural, developing, and urban locations and found that rodent species diversity decreased with increasing urbanization—from 10 species in the rural location to 4 in the rural location. Notably, two species appeared to thrive in urban areas, as follows: the invasive urban exploiter Rattus rattus (n = 375) and the native urban adapter Sundamys muelleri (n = 331). R. rattus was strongly associated with built infrastructure across the gradient and carried a high diversity of pathogens, including multihost zoonoses capable of environmental transmission (e.g., Leptospira spp.). In contrast, S. muelleri was restricted to green patches where it was found at high densities and was strongly associated with the presence of ticks, including the medically important genera Amblyomma, Haemaphysalis, and Ixodes. Our analyses reveal that zoonotic disease risk is elevated and heterogeneously distributed in urban environments and highlight the potential for targeted risk reduction through pest management and public health messaging.